2006
DOI: 10.1002/jms.1001
|View full text |Cite
|
Sign up to set email alerts
|

Semiquantitative analysis of isomeric oligosaccharides by negative‐ion mode UV‐MALDI TOF postsource decay mass spectrometry and their fragmentation mechanism study at N‐acetyl hexosamine moiety

Abstract: Postsource decay (PSD) spectra of isomeric neutral lactooligosaccharide mixtures were measured from the chlorinated molecules [M + Cl]- by negative-ion mode ultraviolet matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (UV-MALDI TOF MS) to estimate quantitatively the mixing ratios in their mixtures. The PSD ions specific to each isomeric structure were used to distinguish the linkage and branching isomers, and the molar ratios of the isomers were estimated from their ion abundances. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 25 publications
1
24
0
Order By: Relevance
“…On the contrary, when subjected to PSD fragmentation in the negative ion mode, prominent cross-ring cleavages are usually produced along with glycosyl bond cleavages. PSD of both deprotonated molecules and anionic adducts of oligosaccharides has been performed and some success for differentiation of linkage positions as well as anomeric configurations in oligosaccharides has been shown [35][36][37][38][43][44][45].…”
mentioning
confidence: 99%
“…On the contrary, when subjected to PSD fragmentation in the negative ion mode, prominent cross-ring cleavages are usually produced along with glycosyl bond cleavages. PSD of both deprotonated molecules and anionic adducts of oligosaccharides has been performed and some success for differentiation of linkage positions as well as anomeric configurations in oligosaccharides has been shown [35][36][37][38][43][44][45].…”
mentioning
confidence: 99%
“…1)῍5), 7) On the basis of these results, we discarded the possibility of the assignment to a Y-type fragmentation.…”
Section: Resultsmentioning
confidence: 99%
“…Second important property of commercially available purified compounds is their known amount. Thus, appropriate calibration curves/mixtures may be constructed for advanced MALDI MS studies as well [82,83]. Although LC-MS combined with bioinformatic tools represents a state-of-the-art screening tool, state-of-the-art MALDI MS methods are more appropriate for detailed structural characterization of previously uncharacterized biomolecules.…”
Section: Purification and Separation Of Pmol Amounts And Microliter Smentioning
confidence: 99%
“…However, for more detailed analyses, and especially quantitative ones, appropriate calibration mixtures with known amounts of individual structures are required. An example of such study is shown in Figure 19 [83], where various mixtures of three isomers, lacto-N-monofucosylpentaose I, II and III were analyzed, based on which the respective calibration curves were constructed. Although these proof-of-concept studies show encouraging data, in order to be able to utilize this approach reliably, all~500 HMO structures must be commercially available in a purified form.…”
Section: Requirement For High Purity Standards In Ms and Lc-ms Researchmentioning
confidence: 99%